2000
DOI: 10.1016/s0168-6496(00)00056-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbial community of lotic organic aggregates ('river snow') in the Elbe River of Germany by cultivation and molecular methods

Abstract: Aerobic and anaerobic cultivation techniques, 16S rDNA‐based phylogeny, and fluorescent in situ hybridization were used to describe the phylogenetic diversity and physiological versatility of lotic microbial aggregates (‘river snow’) obtained from the river Elbe. In the course of the year the ‘river snow’ community changed. It was characterized by a great bacterial diversity in spring, the predominant occurrence of algae in summer and reduction of the total bacterial cell count in autumn and winter. In all ‘ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
83
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 0 publications
18
83
1
Order By: Relevance
“…Using fluorescent in situ hybridization, Böckelmann et al (2000), in the Elbe River of Germany, found that the bacterial aggregate community varied over the course of the year. During all seasons, -proteobacteria constituted the numerically most important bacterial group constituting ~54% of the total DAPI-stainable cells.…”
Section: Estuaries and Riversmentioning
confidence: 99%
“…Using fluorescent in situ hybridization, Böckelmann et al (2000), in the Elbe River of Germany, found that the bacterial aggregate community varied over the course of the year. During all seasons, -proteobacteria constituted the numerically most important bacterial group constituting ~54% of the total DAPI-stainable cells.…”
Section: Estuaries and Riversmentioning
confidence: 99%
“…In this regard, many studies have demonstrated that knowledge of the structure and dynamics of the microbial community in rivers and streams is essential, mainly due to their role in several biogeochemical cycles (Brümmer et al, 2000;Araya et al, 2003;Kostanjšek et al, 2005). This is especially important for environments modified by anthropogenic action (Böckelmanna et al, 2000;Kenzaka et al, 2001;Tiquia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods based on microbiological culture cannot provide a representative composition of the microbial community (Böckelmanna et al, 2000). Alternatively, molecular biology techniques can be used.…”
Section: Introductionmentioning
confidence: 99%
“…A 0.5-liter subsample for determinations of bacterial numbers and OA abundance was fixed immediately with a final concentration of 2.0% formaldehyde. The method for collecting the aggregates was modified after Bö ckelmann et al (2000). To avoid undue influence from the planktonic bacteria in the water column, the major part of the lake water was discarded after 1-h sedimentation.…”
Section: Methodsmentioning
confidence: 99%
“…500 mm) harbor specific aggregate-adapted microbial populations. For example, Betaproteobacteria were the numerically most important bacterial group in lotic microbial aggregates (river snow) from the Elbe River (Bö ckelmann et al 2000), and in lake macroaggregates (lake snow) from the Lake Constance (Weiss et al 1996;Schweitzer et al 2001), whereas Cytophaga, Planctomyces, and Gammaproteobacteria dominated in phytodetrital macroaggregates (marine snow) from the Santa Barbara Channel (Delong et al 1993).…”
mentioning
confidence: 99%